Pengabaian Kemahiran Mendengar dan Bertutur dalam Bilik Darjah di Sekolah Menengah: Punca, Masalah dan Kesannya di Malaysia - Peng, Chew Fong; Othman, Abdul Jalil (SOSIOHUMANIKA, 2008)
ABSTRACT: Listening, speaking, reading and writing are the four basic competency skills in the teaching and learning process of the Malay Language in schools. However, listening and speaking skills tend to be neglected either in primary or secondary schools, but the situation in secondary schools are more serious. This study is carried out to observe the causes, problems and effects of the negligence of listening and speaking skills among the secondary schools students. Descriptive statistic analysis shows that the native speakers gain a higher score in the two skills compared to non-native speakers. The main cause that teachers neglect these skills is students dislike to give their opinions verbally due to their poor mastery of vocabulary and lack of self-confidence. Teachers are regarded as not spending their time in teaching listening and speaking skills in class and they tend to focus more on reading and writing skills. This problem occurs as a result of the fact that no courses about the two skills were organised by Education Ministry and the examination-oriented system. On studentsâ view, they are facing the interference of their mother tongue language. Hence forth, the Education Minister, the State Education Department, teachers and students need to pursue high awareness about the importance of mastering the listening and speaking skills because these skills are the most important and they are the basic skills in our daily life.Key words: listening, speaking, reading and writingâs competencies, and the problems and effects of the negligence all of it among the Malaysianâs secondary schools students.Â Â About the Authors: Dr. Chew Fong Peng ialah Pensyarah di Fakulti Pendidikan UM (Universiti Malaya), Kuala Lumpur, Malaysia. Beliau dilahirkan di Klang, Selangor, Malaysia pada 21hb November 1971. Beliau berkelulusan Ph.D. daripada Pusat Pengajian Bahasa, Kesusasteraan dan Kebudayaan Melayu (PPKKM) UKM Bangi pada tahun 2003. Tajuk thesis Ph.D. beliau adalah âPeranan Sastera Kebangsaan dan Persepsi dalam Pembentukan Perpaduan Nasional: Satu Kajian di Negeri Selangor dan Wilayah Persekutuan Kuala Lumpurâ. Beliau boleh dihubungi dengan alamat e-mail: fpchew@um.edu.my Dr. Abdul Jalil Othman ialah Pensyarah di Fakulti Pendidikan UM (Universiti Malaya), Kuala Lumpur, Malaysia. Dilahirkan di Kedah, Malaysia pada 4hb Mac 1959. Beliau berkelulusan B.Ed.(Hons.) dan M.Ed. daripada UPM (Universiti Putra Malaysia) Serdang, Selangor, pada tahun 1991 dan 1997; dan Ph.D. daripada UM (Universiti Malaya), Kuala Lumpur, pada tahun 2007. Tajuk tesis Ph.D. beliau adalah âPerkaitan Semantik dalam Penulisan Bahasa Melayu Pelajar Ijazah Dasarâ. Beliau boleh dihubungi dengan alamat e-mail: jalil@um.edu.myHow to cite this article? Peng, Chew Fong & Abdul Jalil Othman. (2008). âPengabaian Kemahiran Mendengar dan Bertutur dalam Bilik Darjah di Sekolah Menengah: Punca, Masalah dan Kesannya di Malaysiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.1, No.1 [Mei]. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112, pp.167-192.Chronicle of the article: Accepted (March 15, 2008); Revised (April 18, 2008); and Published (May 20, 2008).